2016
DOI: 10.20892/j.issn.2095-3941.2016.0079
|View full text |Cite
|
Sign up to set email alerts
|

Leptin influences estrogen metabolism and increases DNA adduct formation in breast cancer cells

Abstract: Objective: The elevated incidence of obesity has been paralleled with higher risks of breast cancer. High adiposity increases leptin secretion from adipose tissue, which in turn increases cancer cell proliferation. The interplay between leptin and estrogen is one of the mechanisms through which leptin influences breast carcinogenesis. An unbalanced estrogen metabolism increases the formations of catechol estrogen quinones, DNA adducts, and cancer mutations. This study aims to investigate the effect of leptin o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…com.mx open www.nature.com/scientificreports www.nature.com/scientificreports/ of cancer cells and not of normal breast cells, which is indicative that leptin participates directly in the development of this type of cancer 8,9 .…”
mentioning
confidence: 99%
“…com.mx open www.nature.com/scientificreports www.nature.com/scientificreports/ of cancer cells and not of normal breast cells, which is indicative that leptin participates directly in the development of this type of cancer 8,9 .…”
mentioning
confidence: 99%
“…Obesity has a more serious impact on postmenopausal women than premenopausal women suffering from breast cancer (13,18), which is caused by the different levels of estrogen secretion, and leptin plays a key role in this process. Leptin increases the risk of breast cancer by increasing the effect of hormone secretion on breast tissue hyperplasia, which is more significant in postmenopausal women (22). Before menopause, the body maintains a balance of estrogen levels through the negative feedback regulation mechanism of the hypothalamus-pituitary-gonad axis.…”
Section: Leptin and Tumorigenesismentioning
confidence: 99%
“…Furthermore, leptin is known to upregulate CYP1B1 expression in breast cancer cells. 127 Therefore, the increase in leptin levels in obesity may contribute to the increase in CYP1B1 expression observed. We have shown that CYP1B1 is also highly expressed in adipose tissue, and thoracic adipose tissue from obese mice produces 16OHE1.…”
Section: Adipose-derived Estrogens and Pahmentioning
confidence: 99%
“… 130 , 131 The adipokine leptin has been shown to decrease COMT expression in breast cancer cells. 127 Therefore, the increased leptin levels observed in obesity may result in a reduction in COMT and a decrease the levels of the 2MeOE2, thus attenuating its protective effects on the pulmonary circulation and resulting in a more proproliferative environment that contributes to the development of PAH.…”
Section: Adipose-derived Estrogens and Pahmentioning
confidence: 99%